2019
DOI: 10.1371/journal.pone.0201504
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Chanling Gao on the proliferation and liver metastasis of transplanted colorectal cancer in nude mice

Abstract: This study aimed to explore the efficacy and mechanism of Chanling Gao (CLG), a compound Chinese medicine, on colorectal cancer (CRC). A model of transplanted CRC was established in nude mice. The mice were treated 7 days after CRC transplantation with either Capecitabine or CLG for 3 weeks. On the 28th day after the operation, CRC growth and liver metastasis were assessed by morphology, the changes in the expression of HIF-1α (hypoxia inducible factor-1α), stromal cell–derived factor-1 alpha (SDF-1α), CXCR4 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Modern pharmacological research suggests that the active constituents of the main components of CLG, such as Chan Pi (Toad Skin), Wei Ling Xian (Clematis chinensis), Ge Gen (Radix Puerariae), Chuan Xiong (Ligusticum chuanxiong Hort), and E Zhu(Curcuma aeruginosa Roxb) exhibit anti-tumor effects that reduce the side effects of chemotherapy and improve immunity (Cao et al, 2015;Lee et al, 2015;Zhang et al, 2018;Hao et al, 2019;Zhan et al, 2020). Our previous study demonstrated that the clinical application of CLG (Huang et al, 2016;Yang et al, 2016;Yang et al, 2019) exhibited a certain relief effect in patients with cancer pain and a significant effect on a colorectal cancer nude mouse model. The HPLC (Supplementary Material: Figure 1, Tables 1 and 2) analysis of CLG indicated (Figure 1A) that this extract mainly contained bufogenins [bufalin (0.47 mg/ml), resibufogenin (0.49 mg/ml), telocinobufagin (0.32 mg/ml), gamabufotalin (0.28 mg/ml), arenobufagin (0.36 mg/ml)] (Figures 1a-e), flavonoids [scutellarin (0.26 mg/ml), apigenin (0.65 mg/ml), kaempferol-7-O-b-D-glucopyranoside (0.41 mg/ml), calycosin (1.37 mg/ml), formononetin (0.44 mg/ml), and nobiletin (0.72 mg/ml)] (Figures 1f-k), alkaloids [ammothamnine (0.36 mg/ml) and magnoflorine (0.98 mg/ml)] (Figures 1l, m) as well as other ingredients, such as emodin (0.39 mg/ml), adenosine (0.56 mg/ ml), 9-Oxo-10(E),12(E)-octadecadienoic acid (0.18 mg/ml), cryptotanshinone (0.55 mg/ml), and diosgenin (0.58 mg/ml) (Figures 1n-r).…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological research suggests that the active constituents of the main components of CLG, such as Chan Pi (Toad Skin), Wei Ling Xian (Clematis chinensis), Ge Gen (Radix Puerariae), Chuan Xiong (Ligusticum chuanxiong Hort), and E Zhu(Curcuma aeruginosa Roxb) exhibit anti-tumor effects that reduce the side effects of chemotherapy and improve immunity (Cao et al, 2015;Lee et al, 2015;Zhang et al, 2018;Hao et al, 2019;Zhan et al, 2020). Our previous study demonstrated that the clinical application of CLG (Huang et al, 2016;Yang et al, 2016;Yang et al, 2019) exhibited a certain relief effect in patients with cancer pain and a significant effect on a colorectal cancer nude mouse model. The HPLC (Supplementary Material: Figure 1, Tables 1 and 2) analysis of CLG indicated (Figure 1A) that this extract mainly contained bufogenins [bufalin (0.47 mg/ml), resibufogenin (0.49 mg/ml), telocinobufagin (0.32 mg/ml), gamabufotalin (0.28 mg/ml), arenobufagin (0.36 mg/ml)] (Figures 1a-e), flavonoids [scutellarin (0.26 mg/ml), apigenin (0.65 mg/ml), kaempferol-7-O-b-D-glucopyranoside (0.41 mg/ml), calycosin (1.37 mg/ml), formononetin (0.44 mg/ml), and nobiletin (0.72 mg/ml)] (Figures 1f-k), alkaloids [ammothamnine (0.36 mg/ml) and magnoflorine (0.98 mg/ml)] (Figures 1l, m) as well as other ingredients, such as emodin (0.39 mg/ml), adenosine (0.56 mg/ ml), 9-Oxo-10(E),12(E)-octadecadienoic acid (0.18 mg/ml), cryptotanshinone (0.55 mg/ml), and diosgenin (0.58 mg/ml) (Figures 1n-r).…”
Section: Introductionmentioning
confidence: 99%
“…Its effect mechanism was probably related to the inhibition of SDF-1a, CXCR4, and other protein expression. 22 Furthermore, we also proved that CLG had a significant analgesic impact on Walker 256 breast cancer cells in a rat model of cancer pain, and the HPLC analysis of CLG revealed its primary constituents.…”
Section: Introductionmentioning
confidence: 63%
“…Relevant studies have pointed out that the activation of SDF-1 α /CXCR4 axis in either human breast cancer cell lines or prostate cancer cell lines promotes VEGF secretion to participate in tumor angiogenesis [ 14 , 15 ]. In addition, it has been reported that peritoneal metastasis in gastric cancer proves to be related to the interaction between VEGF, CXCR4, and CXCL12.…”
Section: Discussionmentioning
confidence: 99%